Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Explore our Q&A platform to find reliable answers from a wide range of experts in different fields. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Certainly! Let's solve the given system of equations using the elimination method. The system of equations is:
[tex]\[ \begin{array}{l} -3x + 2y = 9 \\ x + y = 12 \end{array} \][/tex]
### Step-by-Step Solution
1. Label the equations for reference:
[tex]\[ \begin{array}{l} -3x + 2y = 9 \quad \text{(Equation 1)} \\ x + y = 12 \quad \text{(Equation 2)} \end{array} \][/tex]
2. Eliminate one variable:
To eliminate [tex]\(x\)[/tex], we can multiply Equation 2 by 3 so that the coefficients of [tex]\(x\)[/tex] will be opposites. This will allow us to add the equations and eliminate [tex]\(x\)[/tex].
[tex]\[ 3(x + y) = 3 \cdot 12 \][/tex]
Simplifying, we get:
[tex]\[ 3x + 3y = 36 \quad \text{(Equation 3)} \][/tex]
3. Add Equation 1 and Equation 3:
[tex]\[ \begin{array}{rcl} -3x + 2y & = & 9 \\ 3x + 3y & = & 36 \\ \hline 0x + 5y & = & 45 \end{array} \][/tex]
Simplifying, we get:
[tex]\[ 5y = 45 \][/tex]
Solving for [tex]\(y\)[/tex]:
[tex]\[ y = \frac{45}{5} = 9 \][/tex]
4. Substitute [tex]\(y\)[/tex] back into one of the original equations to solve for [tex]\(x\)[/tex]:
We can use Equation 2:
[tex]\[ x + y = 12 \][/tex]
Substituting [tex]\(y = 9\)[/tex]:
[tex]\[ x + 9 = 12 \][/tex]
Solving for [tex]\(x\)[/tex]:
[tex]\[ x = 12 - 9 = 3 \][/tex]
### Solution
The solution to the system of equations is [tex]\((x, y) = (3, 9)\)[/tex].
So, the correct answer is:
[tex]\[ (3, 9) \][/tex]
Therefore, among the given choices:
- [tex]\((-3, 0)\)[/tex]
- [tex]\((1, 6)\)[/tex]
- [tex]\((3, 9)\)[/tex]
- [tex]\((5, 7)\)[/tex]
The correct solution is [tex]\((3, 9)\)[/tex].
[tex]\[ \begin{array}{l} -3x + 2y = 9 \\ x + y = 12 \end{array} \][/tex]
### Step-by-Step Solution
1. Label the equations for reference:
[tex]\[ \begin{array}{l} -3x + 2y = 9 \quad \text{(Equation 1)} \\ x + y = 12 \quad \text{(Equation 2)} \end{array} \][/tex]
2. Eliminate one variable:
To eliminate [tex]\(x\)[/tex], we can multiply Equation 2 by 3 so that the coefficients of [tex]\(x\)[/tex] will be opposites. This will allow us to add the equations and eliminate [tex]\(x\)[/tex].
[tex]\[ 3(x + y) = 3 \cdot 12 \][/tex]
Simplifying, we get:
[tex]\[ 3x + 3y = 36 \quad \text{(Equation 3)} \][/tex]
3. Add Equation 1 and Equation 3:
[tex]\[ \begin{array}{rcl} -3x + 2y & = & 9 \\ 3x + 3y & = & 36 \\ \hline 0x + 5y & = & 45 \end{array} \][/tex]
Simplifying, we get:
[tex]\[ 5y = 45 \][/tex]
Solving for [tex]\(y\)[/tex]:
[tex]\[ y = \frac{45}{5} = 9 \][/tex]
4. Substitute [tex]\(y\)[/tex] back into one of the original equations to solve for [tex]\(x\)[/tex]:
We can use Equation 2:
[tex]\[ x + y = 12 \][/tex]
Substituting [tex]\(y = 9\)[/tex]:
[tex]\[ x + 9 = 12 \][/tex]
Solving for [tex]\(x\)[/tex]:
[tex]\[ x = 12 - 9 = 3 \][/tex]
### Solution
The solution to the system of equations is [tex]\((x, y) = (3, 9)\)[/tex].
So, the correct answer is:
[tex]\[ (3, 9) \][/tex]
Therefore, among the given choices:
- [tex]\((-3, 0)\)[/tex]
- [tex]\((1, 6)\)[/tex]
- [tex]\((3, 9)\)[/tex]
- [tex]\((5, 7)\)[/tex]
The correct solution is [tex]\((3, 9)\)[/tex].
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.